Postoperative Hospital Outcomes of Elective Surgery for Nonmalignant Colorectal Polyps: Does the Burden Justify the Indication?. (13th September 2021) - Kruger, Andrew J.; Hussan, Hisham; Stanich, Peter P.; Gray, Darrell M.; Porter, Kyle M.; Hinton, Alice; Raju, Gottumukkala S.; Krishna, Somashekar G.
Abstract : INTRODUCTION: Despite the increasing availability of advanced endoscopic resections and its favorable safety profile, surgery for nonmalignant colorectal polyps has continually increased. We sought to evaluate readmission rates and outcomes of elective surgery for nonmalignant colorectal polyps on a national level in the United States. METHODS: The Nationwide Readmissions Database (2010–2014 [ International Classification of Diseases, Ninth Revision ] and 2016–2018 [ International Classification of Diseases, 10th Revision ]) was used to identify all adult subjects (age ≥18 years) who underwent elective surgical resection of nonmalignant colorectal polyps. Multivariable analyses were performed for predictors of postoperative morbidity and 30-day readmission. RESULTS: Elective surgery for nonmalignant colorectal polyps was performed in 108, 468 subjects from 2010 to 2014 and in 54, 956 subjects from 2016 to 2018, most of whom were laparoscopic. Postoperative morbidity and 30-day readmission rates were 20.5% and 8.5% from 2010 to 2014, and 13.0% and 7.6% from 2016 to 2018, respectively. Index admission mortality rates were 0.3–0.4%; mortality rates were higher in those with postoperative morbidity. Multivariable analyses revealed that male sex, ≥3 comorbidities, insurance status, and open surgery predicted an increased risk of both postoperative morbidity and 30-day readmission. In addition, postoperative morbidity (2010–2014 [odds ratio 1.58; 95% confidence interval 1.44–1.74] and 2016–2018 [odds ratio 1.55; 95% confidence interval 1.37–1.75]) predicted early readmission. DISCUSSION: In this investigation of national practices, elective surgery for nonmalignant colorectal polyps remains common. There is considerable risk of adverse postoperative outcomes, which highlights the importance of increasing awareness of the range of endoscopic resections and referring subjects to expert endoscopy centers.